"Be free together rather than confined together": A qualitative exploration of how relationships changed in the early COVID-19 pandemic. (October 2021) - Vowels, Laura M.; Francois-Walcott, Rachel R. R.; Perks, Rhia E.; Carnelley, Katherine B.
Due to the COVID-19 pandemic, many couples are staying at home together for an extended period. This is likely to impact couples as they navigate their responsibilities while maintaining a healthy relationship during uncertain times. We conducted qualitative research to investigate participants' perception on how relationships changed considering COVID-19 and social distancing measures. Data were collected through open-ended surveys ( n = 200) which were completed weekly for 5 weeks and by semi-structured interviews ( n = 48). Overall, 28.6% of relationships had gotten better, 28.6% worse, 29.9% stayed the same, and 8.0% were mixed. Both methods highlighted similar themes (communication, space, togetherness, sharing responsibilities, quality time, and support networks) including 15 sub-themes in the interviews. The study provides a unique insight into the impact of COVID-19 on relationships and provides techniques that have been identified by couples to increase relationship satisfaction for their own and others' relationships.